2018
DOI: 10.4187/respcare.06297
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Body Mass Index Decreases Duration of Apneas and Hypopneas in Obstructive Sleep Apnea

Abstract: BACKGROUND: Obesity is one of the most prominent risk factors for obstructive sleep apnea (OSA). Weight loss decreases the number of shorter respiratory events (<40 s), whereas the number of longer events remains almost unchanged. However, it is unknown how body mass index (BMI) affects individual obstruction event severity within OSA severity categories when age, sex, smoking, daytime sleepiness, snoring, hypertension, heart failure, and sleeping posture are considered. Therefore, we investigated whether indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
3
10
1
Order By: Relevance
“…A retrospective study reported a direct relationship of age with OSAS prevalence and that the OSAS prevalence was 13% in participants aged 30e70 y [56]. This confirms the influence of age but also the influence of BMI on the AHI, OSAS severity, and snoring (apneic and non-apneic) [57]. These findings are consistent with a positive correlation of OSAS severity with BMI; in other words, patients with OSAS had higher BMI values than patients with PS [32].…”
Section: Treatment Outcomessupporting
confidence: 61%
“…A retrospective study reported a direct relationship of age with OSAS prevalence and that the OSAS prevalence was 13% in participants aged 30e70 y [56]. This confirms the influence of age but also the influence of BMI on the AHI, OSAS severity, and snoring (apneic and non-apneic) [57]. These findings are consistent with a positive correlation of OSAS severity with BMI; in other words, patients with OSAS had higher BMI values than patients with PS [32].…”
Section: Treatment Outcomessupporting
confidence: 61%
“…The association found between BMI and AHI was also consistent with previous reports. 14 Thus, this study has shown that although there was initially no significant association between the Mallampati score and AHI found in a previous report, 1 an association between the Mallampati score and the mouth opening capacity and between BMI and AHI does exist. Physicians should consider the extent of mouth opening when assessing OSA based on the Mallampati score.…”
Section: Discussioncontrasting
confidence: 50%
“…Hypertension has been strongly linked to OSA and the prevalence of hypertension increases with increasing severity of OSA [22,23]. In OSA patients, it has been reported that sympathetic activity is elevated during sleep due to repeated inspiratory efforts against obstructed airways, hypoxia, and respiratory event-related arousals [22].…”
Section: Discussionmentioning
confidence: 99%